IRGM Gene Variants Modify the Relationship Between Visceral Adipose Tissue and NAFLD in Patients With Crohn's Disease. Issue 10 (18th May 2018) - Simon, Tracey G; Van Der Sloot, Kimberley W J; Chin, Samantha B; Joshi, Amit D; Lochhead, Paul; Ananthakrishnan, Ashwin N; Xavier, Ramnik; Chung, Raymond T; Khalili, Hamed
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is an increasingly recognized comorbidity in Crohn's disease (CD), but the mechanisms are poorly understood. Autophagy is a highly conserved process regulating innate immunity that contributes to CD susceptibility. Emerging data suggest that variants in the autophagy-governing IRGM gene may contribute to the accumulation of visceral adipose tissue (VAT) and hepatic fat. Our objective was to characterize the relationship between VAT, IRGM gene variants, and NAFLD risk in patients with CD. Methods: We included all CD patients in the Prospective Registry in Inflammatory Bowel Disease Study at Massachusetts General Hospital (PRISM) without history of alcohol abuse or liver disease. Hepatic fat was quantified by liver attenuation (LA) on computed tomography, with NAFLD defined by the validated liver:spleen (L:S) ratio. NAFLD severity was estimated by the FIB-4 Index and alanine aminotransferase (ALT). Using logistic regression modeling, we examined the relationship between VAT, autophagy gene variants, and NAFLD risk. Results: Among 462 patients, 52% had NAFLD. Increasing VAT quartile was associated with reduced LA (mean change, –7.43; 95% confidence interval [CI], –10.05 to –4.81; P trend < 0.0001). In the fully adjusted model, patients in the highest VAT quartile had a 2.2-fold increased NAFLD risk (95% CI, 1.21 to 4.14; P trend = 0.032) and a 4.2-fold increased risk of ALT>upper limit of normal (ULN) (95% CI, 1.19 to 14.76; P trend = 0.017). The relationship between VAT and NAFLD was modified by IRGM variants rs4958847 and rs13361189 ( P interaction = 0.005 and P interaction < 0.001, respectively). Conclusions: In a large CD cohort, VAT was directly associated with prevalent NAFLD, and this relationship was augmented by functionally annotated IRGM variants associated with impaired autophagy.